2013
DOI: 10.1007/s00705-013-1923-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of a putative nucleolar localization signal in the coat protein of ourmia melon virus

Abstract: Ourmiaviruses became the object of recent attention for their unusual taxonomic placements among plant viruses. The ourmia melon virus (OuMV) RNA3 encodes a 22-kDa coat protein (CP). Besides its role in virion formation, the OuMV CP facilitates systemic virus spread. In Nicotiana benthamiana, an eGFP-CP fusion protein was localized in the nucleus and preferentially in the nucleolus. By bioinformatics analysis, we identified an arginine-and lysine-rich region at the N-terminus of the CP. Here, we demonstrate by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…Well-characterized plant virus proteins of this category include the ORF3 protein of Groundnut rosette virus (GRV; unassigned family, genus Umbravirus), the CP of Potato leaf roll virus (family Luteoviridae), the genome-linked viral protein of Potato virus A (family Potyviridae), the 2b suppressor of RNA silencing of Cucumber mosaic virus (family Bromoviridae), the P7a movement protein of Beet black scorch virus (family Tombusviridae), the CP of Alfalfa mosaic virus (family Bromoviridae), the P30 movement protein encoded by Turnip vein clearing virus (family Virgaviridae), and the P14 suppressor of RNA silencing and P25 of Beet necrotic yellow vein virus (family Virgaviridae; Haupt et al, 2005b;Kim et al, 2007;Rajamäki and Valkonen, 2009;González et al, 2010;Herranz et al, 2012;Wang et al, 2012;Chiba et al, 2013;Levy et al, 2013). Other viral proteins found in the nucleolus include the P3 protein of Tobacco etch virus (family Potyviridae) and the CP of Ourmia melon virus (unassigned family, genus Ourmiavirus), but the function of these nucleolar localizations is unknown (Taliansky et al, 2010;Crivelli et al, 2011;Rossi et al, 2014). Another nucleolus-localized …”
Section: Discussionmentioning
confidence: 99%
“…Well-characterized plant virus proteins of this category include the ORF3 protein of Groundnut rosette virus (GRV; unassigned family, genus Umbravirus), the CP of Potato leaf roll virus (family Luteoviridae), the genome-linked viral protein of Potato virus A (family Potyviridae), the 2b suppressor of RNA silencing of Cucumber mosaic virus (family Bromoviridae), the P7a movement protein of Beet black scorch virus (family Tombusviridae), the CP of Alfalfa mosaic virus (family Bromoviridae), the P30 movement protein encoded by Turnip vein clearing virus (family Virgaviridae), and the P14 suppressor of RNA silencing and P25 of Beet necrotic yellow vein virus (family Virgaviridae; Haupt et al, 2005b;Kim et al, 2007;Rajamäki and Valkonen, 2009;González et al, 2010;Herranz et al, 2012;Wang et al, 2012;Chiba et al, 2013;Levy et al, 2013). Other viral proteins found in the nucleolus include the P3 protein of Tobacco etch virus (family Potyviridae) and the CP of Ourmia melon virus (unassigned family, genus Ourmiavirus), but the function of these nucleolar localizations is unknown (Taliansky et al, 2010;Crivelli et al, 2011;Rossi et al, 2014). Another nucleolus-localized …”
Section: Discussionmentioning
confidence: 99%
“…A link between the ability to interact with the nucleolus and the outcome of viral infection has been established in many cases (Hiscox, 2007;Salvetti and Greco, 2014). In recent years, diverse plant viruses belonging to different genera or families have also been found to encode one or multiple proteins localizing to the nucleolus (Martínez and Daròs, 2014;Rossi et al, 2014;Taliansky et al, 2010;and references therein). In the nucleolus, Groundnut rosette virus (GRV, an umbravirus) open reading frame 3 (ORF3) interacts with fibrillarin and recruits this nucleolar protein to form infectious ribonucleoproteins (RNPs) in the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…For most other plant viruses, the rationale for their nucleolus targeting is currently unclear. However, a growing number of correlative studies have indicated that the nucleolus may play a role in many steps in the infection cycle of these viruses (Martínez and Daròs, 2014;Rossi et al, 2014;Taliansky et al, 2010;and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Such intracellular targeting seems to be determined by a short stretch of amino acids at the N-terminal region of the protein. This region is rich in lysine and arginine residues and mutations of only three amino acids within this region resulted in the complete exclusion of the GFP-CP mutant from the nucleolus (Rossi et al 2014). These results provide a model whereby the OuMV CP has a functional activity in addition to its structural role.…”
mentioning
confidence: 74%
“…benthamiana cells (Rossi et al 2014). In the present work, we used some of the most significant CP mutants from that study (Fig.…”
mentioning
confidence: 99%